Analisis kesulitan siswa SMP dalam menyelesaikan soal aritmetika sosial - Saputri, Hana Febri; Putri, Nathania Salsabila; Riyanti, Asifa Ajeng Dwi; Angraini, Lilis Marina (EDUPEDIA PUBLISHER, 2024)
Purpose: The objective of this research was to investigate the challenges faced by junior high school students in solving social arithmetic problems. Methodology: This research method is a qualitative method with descriptive research type. This research was carried out at one of the Pekanbaru junior high schools with class VII subjects at Da`wah Pekanbaru Middle School, with a total of 30 students. Results: The data collection technique used in this research is a written test technique in the form of a description consisting of 5 questions. After students complete the questions, the answers will be analyzed and when the researcher finds unique answer results, the researcher will conduct an interview. Conclusions: Based on the research results, it was found that students' difficulties in solving social arithmetic problems were 1) difficulty in understanding the information from the questions, 2) difficulty in understanding the concept correctly. 3) lack of accuracy in the solution process and 4) time constraints which cause students to not be able to complete the questions properly and correctly. Recommendations: It is hoped that the results of this research will allow teachers to guide and overcome the difficulties faced by students so that students can develop their abilities in mathematics, especially social arithmetic material.